Now is your time! : the African-American struggle for freedom - Myers, Walter Dean, 1937- (New York : HarperCollins, 1991)
A history of the African-American struggle for freedom and equality, beginning with the capture of Africans in 1619, continuing through the American Revolution, the Civil War, and into contemporary times.
"Coretta Scott King award"--jacket.
Includes bibliographical references (p. [278]-281) and index.
Keywords: African Americans -- History; United States; United States -- Juvenile literature